Beyond the Iron Age: The ecological relevance of bioactive trace metals other than Fe and organic growth factors in aquatic systems - Laura Gomez Consarnau (Frontiers Research Topics, 2015)
In the last three decades, research has extensively focused on the role of Fe and other mineral nutrients in regulating biological processes, ranging from the surface to the deep ocean. This has produced major breakthroughs in our understanding of the fundamental role of those bioactive elements on the carbon, nitrogen and sulfur cycles and ecosystem function. However, biological processes cannot be entirely sustained by that small set of chemical elements, and new scientific evidence suggests that trace metals other than Fe (e.g., Co, Mo and Ni) as well as essential organic growth factors (e.g., vitamins) may also be crucial in most aquatic systems.